PENGARUH MOTIVASI, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN Studi Kasus Pada Karyawan CV. RENS JAYA di Kabupaten Tangerang - Rendy Afrizal; Setyani Dwi Lestari (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study aims to determine the effect of Motivation (X1) on Employee Performance (Y), Work Environment (X2) on Employee Performance (Y), and Work Discipline (X3) on Employee Performance (Y) among employees of CV. Rens Jaya in Tangerang Regency. The research uses a non-probability sampling technique with a saturated sampling method. The population in this study consists of 45 employees working at CV. Rens Jaya in Tangerang Regency. The research was conducted using multiple linear regression analysis, assisted by SPSS version 25 and Microsoft Excel 2016. The results show that Work Motivation (X1) has a positive and significant effect on Employee Performance (Y), the Work Environment (X2) has a positive and significant effect on Employee Performance (Y), and Work Discipline (X3) has a positive effect on Employee Performance (Y).